Definições, dimensões e determinantes da parentalidade - Barroso, Ricardo G. (2010)
It is expected that parents / caregivers facilitate the development of their offspring on the physical, psychological and social levels. The tasks required for this process were designated as “parenting”, that is, the way (process) as the parents / caregivers take care of their child. However, some factors may restrict, and even compromise, these behaviors and tasks. This article presents these dimensions and determinants of parenting, providing a framework of analysis and evaluation of parenting skills for purposes of research and intervention.